Biodiesel Production From the Microalgae Nannochloropsis by Microwave Using CaO and MgO Catalysts - Herman Hindarso; Aylianawati Aylianawati; Martinus Edy Sianto (Center of Biomass & Renewable Energy (CBIORE), 2015)
The needs of world petroleum are increased; in contrast, the fuel productions are getting decreased. Therefore, it has lead to the search for bio-fuel as an alternative energy. There are several different types of biofuel, such as biodiesel, ethanol, bioalcohol, and biogas. Biodiesel is typically made by chemically reacting lipids from a vegetable oil or animal fat with an alcohol producing fatty acid esters, such as methyl or ethyl ester. The present study aimed to study the effect of temperature (50, 60 and 65°C), reaction time (1 to 5 minutes) dan types of catalyst (CaO dan MgO of 1 and 3 %) in the production of biodiesel from microalgae by the transesterification process using microwave methods. It also studied the characteristics of biodiesel which had the greatest yield in the present study, i.e. flash point, cetane number, density, viscosity, and FAME. The greatest yield was 99.35% and obtained with combination of 3% MgO catalyst quantity at temperature of 60°C, in 3 minutes reaction time. At this process conditions, the biodiesel has a flash point of 122°C, cetane number of 55, density of 0.89, viscosity of 5 cP and FAME of 75.12 %.